Low-Dose Chest CT Lung Cancer Screening for School Cafeteria Workers: A Position Paper from the Korean Society of Thoracic Radiology - Won Gi Jeong; Gong Yong Jin; Se Ri Kang; Seung-Jin Yoo; Kyongmin Sarah Beck; Kum Ju Chae; Soyeoun Lim; Jin Young Yoo; Hee Kang; Hongseok Ko; Jae-Kwang Lim; Soo-Youn Ham; et al. (Journal of the Korean Society of Radiology)
The Korean Society of Thoracic Radiology (KSTR) conducted an assessment on the necessity of low-dose chest CT (LDCT) lung cancer screening for Korean school cafeteria workers. This assessment was prompted by growing concerns about the potential risk of lung cancer due to exposure to carcinogenic cooking fumes. To reach a consensus on various aspects of LDCT screening for Korean school cafeteria workers, thoracic radiologists were involved in a survey that utilized the Delphi method. Key issues addressed in the survey included the need for tailored environmental assessments for this specific group, guidelines for interpreting LDCT results, and the evaluation of cooking occupations as a potential risk factor for lung cancer. The survey results revealed a lack of evidence supporting the benefits of LDCT lung cancer screening for Korean school cafeteria workers. Furthermore, there was no consensus reached on the criteria for determining which Korean school cafeteria workers should undergo LDCT screening, guidelines for interpreting the results, or the level of evidence supporting cooking tasks as a risk factor for lung cancer. In this position paper, the KSTR critically examines these aspects and emphasizes the importance of an evidence- based approach to lung cancer screening by considering the unique occupational and environmental context of Korean school cafeteria workers.